Digital Service Innovation and Marketing Performance of Campus Cooperatives: A Descriptive Study Based on Secondary Data - Ekky Noviar; Tohiroh Tohiroh; Syafran Nurrahman (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study aims to analyze digital service innovation and its relationship with the marketing performance of campus cooperatives. The research employed a descriptive quantitative approach using secondary data obtained from financial reports, Annual Member Meeting (RAT) documents, and cooperative activity reports during the 2023–2025 period. Data were analyzed using documentation techniques, descriptive analysis, and trend analysis to examine the development of cooperative revenue, Net Operating Surplus (SHU), and forms of digital innovation implemented by the cooperative. The findings show that campus cooperatives gradually implemented several digital service innovations, including QRIS-based cashless payment systems, digital transaction recording, and social media utilization for promotion and communication. During the study period, cooperative revenue increased from IDR 1,247,350,000 in 2023 to IDR 1,563,480,000 in 2025, accompanied by relatively stable SHU growth. Descriptively, the implementation of digital service innovation was followed by improvements in transaction activity and operational efficiency. However, this study does not statistically test causal relationships because the analysis is limited to descriptive trend analysis based on secondary data. This study implies that digital transformation can become a strategic approach to strengthening the marketing performance and sustainability of campus cooperatives in the digital era